(untitled) (International Journal of Pharmaceutical and Life Sciences, 2013)
Nanoparticle drug carriers consist of solid biodegradable particles in size ranging from 10 to 1000 nm (50300 nm generally). The use of minute particles as drug carriers for targeted treatment has been studied over a long period of time. A selective accumulation of active substances in target tissues has been demonstrated for certain so-called nanocarrier systems that are administered bound to pharmaceutical drugs. Great expectations are placed on nanocarrier systems that can overcome natural barriers such as the blood-brain barrier (BBB) and transport the medication directly to the desired tissue and thus heal neurological diseases that were formerly incurable. Polymeric Nanoparticle have been shown to be promising carriers for CNS drug delivery due to their potential both in encapsulating drugs, hence protecting them from excretion and metabolism, and in delivering active agents across the blood brain barrier without inflicting any damage to the barrier. Different polymers have been used and different strategies like surface modification have been done to increase the retention time of nanoparticles. DOI: http://dx.doi.org/10.3329/ijpls.v2i3.15457 International Journal of Pharmaceutical and Life Sciences Vol.2(3) 2013: 107-132